Особливості індивідуального письма І. Багряного: рання творчість письменника - Гайдіна, С.О.; Шарова, Тетяна Михайлівна; Шарова, Татьяна Михайловна; Sharova, Tetiana (My University, 2021)
UK: У статті розглядаються питання особливостей індивідуального письма І. Багряного. Наголошується на його ранній творчості та виявленні у його творах громадянських позицій. У дослідженні представлена тематика ранньої творчості письменника та виявлені його прагнення у представленні подій тогочасної дійсності. EN: The article considers the peculiarities of I. Bagryany’s individual writing. Emphasis is placed on his early work and the expression of civic positions in his works. The study presents the theme of the writer’s early work and reveals his aspirations to present the events of contemporary reality.
Peculiarities of I. Bagryany’s Individual Writing: Early Creativity of the Writer
Keywords: художня творчість; рання поезія; письменник; поезія; місто; тематика; artistic creativity; early poetry; writer; poetry; city; subject matter